2022
DOI: 10.1177/20503121221088432
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of hypertensive disorders of pregnancy among pregnant women attending antenatal clinic at a tertiary hospital in Ghana

Abstract: Objectives: Hypertensive disorders of pregnancy contribute significantly to maternal and neonatal morbidity and mortality globally. Health-seeking behaviour is influenced by adequate knowledge of the condition. However, current data on pregnant women’s knowledge of the condition and health-seeking behaviour are relatively scant in Ghana and has not been previously studied in the Central Region where hypertensive disorders of pregnancy was the leading cause of maternal mortality from 2016 to 2018. The study sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Previous research has found comparable results. [24][25][26] Previous studies undertaken in South Africa 22 and elsewhere [27][28][29] have found that patients had inadequate understanding regarding PIH, complications, and risk factors. Notably, some of these studies attributed the lack of awareness and knowledge about PIH to misconceptions and myths, such as women believing that PIH is a spiritual condition that requires spiritual treatment 27,30,31 or a sign that a woman is likely to birth a baby boy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found comparable results. [24][25][26] Previous studies undertaken in South Africa 22 and elsewhere [27][28][29] have found that patients had inadequate understanding regarding PIH, complications, and risk factors. Notably, some of these studies attributed the lack of awareness and knowledge about PIH to misconceptions and myths, such as women believing that PIH is a spiritual condition that requires spiritual treatment 27,30,31 or a sign that a woman is likely to birth a baby boy.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of an individual on a particular health condition influences the health seeking behaviour of individual [ 22 ]. Thus, knowledge on HDPs has been assessed as efforts at preventing HDP burden.…”
Section: Discussionmentioning
confidence: 99%
“…The adoption of the 70% cut‐off was based on the preference of the investigators for pregnant women to have rationally adequate knowledge of ANC services considering its significance on maternal and child health. Such relatively arbitrary cut‐off scores have been used to categorize knowledge in previous studies (Afaya et al, 2020; Agbeno et al, 2022; Oppong Asante, 2013; Wolde et al, 2019).…”
Section: Methodsmentioning
confidence: 99%